Development and setting of a time-lapse video camera system for the Antarctic lake observation - Sakae Kudoh; Yukiko Tanabe; Masaki Uchida; Katsuhiro Hori (Antarctic Record, 2010)
A submersible video camera system, which aimed to record the growth image of aquatic vegetation in Antarctic lakes for one year, was manufactured. The system consisted of a video camera, a programmable controller unit, a lens-cleaning wiper with a submersible motor, LED lights, and a lithium ion battery unit. Changes of video camera (High Vision System) and modification of the lens-cleaning wiper allowed higher sensitivity and clearer recording images compared to the previous submersible video without increasing the power consumption. This system was set on the lake floor in Lake Naga Ike (a tentative name) in Skarvsnes in Soya Coast, during the summer activity of the 51th Japanese Antarctic Research Expedition. Interval record of underwater visual image for one year have been started by our diving operation.